Analysis of the Competitiveness and Complementarity of China’s Tea Exports to Malaysia - Yang, Wei; Mohammad Affendy, Arip; Chin Hong, Puah (Macrothink Institute, USA, 2025)
Using trade data on China-Malaysia tea trade from 2015 to 2024, this study employs four key quantitative indices: the Market Share Index (MSI), Revealed Comparative Advantage Index (RCA), Trade Complementarity Index (TCI), and Trade Intensity Index (TII), to evaluate the competitiveness and complementarity of China’s tea exports to Malaysia. The findings indicate that although the competitiveness of China’s tea exports increased with some fluctuations between 2015 and 2022, it experienced a relative decline from 2023 to 2024. In parallel, trade complementarity demonstrated a steady upward trend, indicating a continuously improving alignment in bilateral tea trade. Based on these outcomes, the study proposes policy recommendations focused on areas such as promoting supply-side reforms, improving distribution channels, enhancing brand image, and fostering cultural communication.